Child Restraint System (CRS) Incentive Road Tour Program: Initiatives to Increase the CRS Ownership among Malaysian Parents - N. Shaari; N.F. Paiman; A.H. Abdul Ghani; H. Makhpol; A.M. Radzi; F. Lamin; N. Borhan; N. Jamaluddin; Y. Ahmad (Journal of the Society of Automotive Engineers Malaysia, 2025)
Child restraint systems (CRS) are designed to protect child occupants in the event of a collision, restrain them during sudden stops or maneuvers, and minimize the risk of injury in the event of a crash. This program aims to increase CRS usage among Malaysians and further educate parents on the importance of CRS. The government has introduced an incentive program for the B40 and M40 household groups, which is financial incentive assistance for up to MYR 150 for the purchase of CRS. Malaysian Institute of Road Safety Research (MIROS) has been appointed by the Ministry of Transport (MOT) of Malaysia as the implementing agency. Road Tour Program is one of MIROS’ initiatives to increase the CRS ownership among Malaysian road users through various activities done such as booth promotion and intervention programs, to promote the program. This program received a favorable response from Malaysians, with a total CRS purchase of 63,395 CRS units throughout the incentive program.